Airwave oscillometry and spirometry in children with asthma or wheeze. (3rd June 2023) - Gunawardana, Shannon; Tuazon, Mark; Wheatley, Lorna; Cook, James; Harris, Christopher; Greenough, Anne
Abstract: Objective: Lung function testing is used in diagnosing asthma and assessing asthma control. Spirometry is most commonly used, but younger children can find performing this test challenging. Non-volitional tests such as airwave oscillometry (AOS) may be helpful in that population. We compared the success of spirometry and AOS in assessing bronchodilator responsiveness in children. Methods: AOS was conducted alongside routine lung function testing. Resistance at 5 Hz (R5), the difference between the resistance at 5 and 20 Hz (R5-20) and the area under the reactance curve (AX) were assessed. Patients between 5 and 16 years old attending clinic with wheeze or asthma were assessed. Patients performed AOS, followed by spirometry and were then given 400 µg salbutamol; the tests were repeated 15 minutes later. Results: Lung function testing was performed in 47 children of whom 46 (98%) and 32 (68%) performed acceptable baseline oscillometry and spirometry, respectively ( p  < 0.001). Children unable to perform acceptable spirometry were younger (7.35, range: 5.4–10.3 years) than those who could (10.4, range: 5.5–16.9 years), p  < 0.001. The baseline z-scores of AOS R5 correlated with FEV1 ( r  = 0.499, p  = 0.004), FEF75 ( r  = 0.617, p  < 0.001), and FEV1 /FVC ( r  = 0.618, p  < 0.001). There was a positive bronchodilator response assessed by spirometry (change in FEV1 ≥ 12%) in eight children which corresponded to a change in R5 of 36% (range: 30%–50%) and a change in X5 of 39% (range: 15%–54%). Conclusions: Oscillometry is a useful adjunct to spirometry in assessing young asthmatic children's lung function. The degree of airway obstruction, however, might affect the comparability of the results of the two techniques.